PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD: SEBUAH LITERATUR REVIEW - Marciano, Benny; Syam, Ardiansyah; Ahmar, Nurmala; Gayatri, Maria; Suyanto, Suyanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
Fraud is any action taken illegally for personal gain. Good Corporate Governanceis a set of rules related to the company's control process implementation whichinvolving all stakeholders to ensure the company's performance in achieving theorganization's vision and mission. This study aims to determine the effect of theimplementation of Good Corporate Governance on fraud prevention efforts. This study was conducted through a literature review of 15 published articles. Literaturesearches were carried out on various electronic databases such as Google Scholar,Scopus, ProQuest, ScienceDirect, ACM Digital Library, IEEE Xplore, and Springerby entering keywords, namely "Good Corporate Governance", "Good Governance","Fraud Prevention", "Prevention of Fraud", and “fraud”. The results of theliterature review show that the application of Good Corporate Governance is ableto prevent fraud through the implementation of the principles of Good CorporateGovernance, namely transparency, accountability, responsibility, independence,and fairness. The implementation of good corporate governance can increaseinvestor confidence in making investments. The implementation of Good CorporateGovernance can be a control in controlling the company's performance in achievingtargets and preventing stakeholder losses. The consistent implementation of GoodCorporate Governance can improve employee performance effectively andefficiently as well as generate sustainable economic value and have a positive impacton shareholders and society.